PENGAWASAN USAHA WISATA HIBURAN OLEH PEMERINTAH KOTA DUMAI (STUDI KASUS USAHA KARAOKE) - Zarfandi, Ardian; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Karaoke Entertainment is one of the most popular businesses in Dumai city, it can be proved by the many karaoke business in Dumai city. In running the Karaoke business, the business needs to be supervised by Dumai City Government which is regulated in Mayor Regulation of Dumai Number 21 of 2013 on Procedures and Procedures of Granting Business License of Tourism. Like other entertainment, karaoke business has a negative impact on the norms that exist in society. So in running the business, the business must require supervision. The formulation of the problem in this research are: 1. How the Supervision of Entertainment Tour Business by Dumai City Government About Karaoke Business. 2. What are the factors that influence the Monitoring of Entertainment Tour Enterprises by Dumai City Government About Karaoke Enterprises. This research uses qualitative research methods with descriptive data assessment.The concept of the theory used is according brantas is setting standards that will be used as the basis for monitoring, measuring performance or results that have been achieved, take corrective action. This research uses qualitative research methods with descriptive data assessment.The result of the research shows that the supervision of karaoke entertainment business is done by the Tourism Office, Satpol PP, BPTPM Dumai City not according to the procedure specified in the legislation, after the research, the conclusion in this research are: Implementation of karaoke entertainment supervision conducted by Tourism Office, Satpol PP, BPTPM not yet maximal, supervision conducted by Dumai City Government has not done well. There are factors that become obstacles in the implementation of supervision such as lack of human resources, facilities for supervision is not adequate and lack of coordination with relevant agencies in conducting supervision.Key Word : Supervision, Mayor's Regulation, Karaoke